Who am I becoming?: Understanding the ministry training portfolio as a theological practice - Gibson, Timothy (Theology, 2021)
This article outlines a theological basis for the process of compiling a portfolio as part of a programme of ministerial formation. Such a task can often seem to the candidate rather like jumping through hoops, or gathering evidence merely for the sake of it. But I argue that it is properly understood as a theological practice, inviting reflection on who they are becoming in Christ. In philosophical literature, ‘gestures’ are understood as incomplete actions that correspond to some deeper truth. By framing the task of portfolio composition in the language of ‘gesture’, it is seen to be a vital practice in formation for public ministry, rather than merely an exercise in proving one’s readiness for ordination or licensing.